Effect of walking velocity on ground reaction force variables in the hind limb of clinically normal horses - Khumsap S. (2014)
Objective: To measure the effect of subject velocity on hind limb ground reaction force variables at the walk and to use the data to predict the force variables at different walking velocities in horses. Animals: 5 clinically normal horses. Procedure: Kinematic and force data were collected simultaneously. Each horse was led over a force plate at a range of walking velocities. Stance duration and force data were recorded for the right hind limb. To avoid the effect of horse size on the outcome variables, the 8 force variables were standardized to body mass and height at the shoulders. Velocity was standardized to height at the shoulders and expressed as velocity in dimensionless units (VDU). Stance duration was also expressed in dimensionless units (SDU). Simple regression analysis was performed, using stance duration and force variables as dependent variables and VDU as the independent variable. Results: Fifty-six trials were recorded with velocities ranging from 0.24 to 0.45 VDU (0.90 to 1.72 m/s). Simple regression models between measured variables and VDU were significant (R2 > 0.69) for SDU, first peak of vertical force, dip between the 2 vertical force peaks, vertical impulse, and timing of second peak of vertical force. Conclusion and Clinical Relevance: Subject velocity affects vertical force components only. In the future, differences between the forces measured in lame horses and the expected forces calculated for the same velocity will be studied to determine whether the equations can be used as diagnostic criteria. (Am J Vet Res 2001;62:901-906).